PENGARUH TEKNOLOGI BERBASIS PODCAST TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA PADA BIDANG STUDI AGAMA KRISTEN KELAS XI SMKS IMELDA MEDAN - Christoper Sodipta Manik; Bangun Munthe; Hersakso Sinurat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to see the extent to which Podcast-Based Technology Influences Increasing Student Learning Motivation in the Field of Christian Religion Studies of Class XI of Imelda Vocational High School Medan with a sample of 30 people. This study uses a descriptive quantitative method with a data collection tool using a linkert scale questionnaire in the form of a checklist that has been tested for instrument validation. After the Pearson product moment correlation statistical test was carried out. From the results of the correlation test obtained (r) 0.69 with a determination test of 47.61% and to determine whether the correlation coefficient is significant or not at the level (a) = 0.05, a "t" test was conducted with the testing criteria if the t_count obtained from the calculation is greater (>) than t_table at a significance level of 1-0.05 with dk = n-2 then the hypothesis is accepted and in other cases rejected. From the test results obtained t_count > t_table (9.7> 1.70), then the hypothesis is accepted. Thus, a correlation can be found between the influence of podcast-based technology on improving student learning motivation in the field of Christian studies in grade 11 of SMKS Imelda Medan.